Beyond Conventional Disinfectants: A Comparative Review of Cold Atmospheric Plasma and Photodynamic Therapy against Oral Pathogens: New antimicrobial techniques against oral pathogens - Pourhajibagher , Maryam; Parker, Steven; Bahrami, Rashin; Bahador, Abbas (Journal of Lasers in Medical Sciences, 2026)
Introduction: Microbial resistance is a global challenge for conventional antimicrobial methods such as chlorhexidine (CHX) and sodium hypochlorite (NaOCl). Among the recently developed approaches, photodynamic therapy (PDT) and cold atmospheric plasma (CAP) have garnered attention. This study reviews the effectiveness of CAP and PDT relative to each other and to other antimicrobial methods. Methods: The primary keywords, including “antimicrobial photodynamic therapy,” “cold plasma,” “disinfection,” and “oral pathogens,” were used in a literature search across databases such as Google Scholar and PubMed, covering the period from January 2016 to September 2025. Results: CAP and PDT showed effective antimicrobial effects against oral pathogens. For CAP, main parameters include gas composition (He/O₂), power (55 W), and exposure duration (60-180 seconds). A He/O₂ plasma jet reduced the bacterial load in Enterococcus faecalis biofilms. The efficacy of PDT was different based on the types of photosensitizers and light parameters. Indocyanine green (0.2%) with an 810-nm laser (12 J/cm², 60 s) was effective against Streptococcus mutans, while Methylene blue (0.02%) with a 660-nm laser (20 J/cm², 100 s) showed higher biofilm reduction. Both methods surpassed conventional antimicrobial agents such as CHX and NaOCl, especially in biofilm penetration. Conclusion: CAP and PDT are promising alternatives to conventional antimicrobial methods, offering effective control of oral pathogens with lower side effects than CHX and NaOCl. However, further research is needed to optimize treatment parameters and determine the most suitable clinical applications for each method.